Influence of hematoxylin and eosin staining on linear birefringence measurement of fibrous tissue structures in polarization microscopy - Deng, L; Chen, C; Yu, W; Shao, C; Shen, Z; Wang, Y; He, C; Li, H; Liu, Z; He, H; Ma, H (Society of Photo-optical Instrumentation Engineers, 2023)
Significance For microscopic polarization imaging of tissue slices, two types of samples are often prepared: one unstained tissue section for polarization imaging to avoid possible influence from staining dyes quantitatively and one hematoxylin-eosin (H&E) stained adjacent tissue section for histological diagnosis and structural feature identification. However, this sample preparation strategy requires high-quality adjacent tissue sections, and labeling the structural features on unstained tissue sections is impossible. With the fast development of data driven-based polarimetric analysis, which requires a large amount of pixel labeled images, a possible method is to directly use H&E stained slices, which are standard samples archived in clinical hospitals for polarization measurement.